Structural dynamic monitoring in historical masonry structures using wireless and MEMS technology - Aguilar, Rafael (2009)
For most advanced economies, buildings represent one of the largest single investments of national resources. While recently built buildings are very important, there are other existent structures that require even more attention. The permanent study of ancient buildings, which represents the architectural heritage of a region, is a key aspect to modern societies since the impact of a possible loss is not only economical but also cultural. In the process of preservation of architectural heritage, the damage evaluation and the monitoring procedures are attractive, due to the modern philosophy of minimum repair and the use of non intrusive methods. The developments on Micro-Electro-Mechanical Systems (MEMS) and the increasing interest in the scientific community on improve wireless transmission technologies make this field interesting for the structural monitoring. Since 2003, the Civil Engineering Department of the University of Minho (UMINHO) has been involved in performing static and dynamic monitoring tests of historical masonry structures. For what concerns to the dynamic monitoring, Output-Only methods with conventional wired based sensors and data acquisition platforms have been used in several monuments in Portugal even in abroad with successful results. In 2007, the PhD project was initiated with the aim of use the new technology based on wireless platforms with embedded MEMS to perform dynamic monitoring tests. The following results presented in this paper belong to this study.